Modern ideas of the role of the immune process and hemostasis in the pathogenesis of sepsis - M. V. Osikov; L. F. Telesheva; A. G. Konashov; A. V. Gusev; V. A. Konashov (Acta Biomedica Scientifica, 2024)
The pathogenesis of sepsis as a pathological process, which is based on the body’s reaction in the form of generalized (systemic) inflammation to an infection of various nature, leading to acute multi-organ dysfunction, includes changes in the immune response, imbalance of  pro-inflammatory and  anti-inflammatory mechanisms, hemostasis disorders, hemodynamic disorders, microcirculation, activation of the hypothalamic-pituitary-adrenal system, and disorders of delivery, consumption, and utilization of oxygen. The predominance of the pro-inflammatory component over the anti-inflammatory one and damage to the primary barrier structures in the area of inflammation predetermines the breakthrough of inflammatory mediators into the  systemic circulation. The  dominance of  the  destructive effects of  cytokines leads to a disorder of microcirculatory hemodynamics outside the primary focus, to the launch of disseminated vascular coagulation syndrome and organ failure. Sepsis is characterized by a hypercoagulable-hypofibrinolytic phenotype of changes in hemostasis, immunothrombosis as a result of endothelial dysfunction, platelet activation, autocoid-induced coagulation, activation of the external and internal coagulation pathways, and a decrease in the activity of the anticoagulation and fibrinolytic systems. Tumor necrosis factor α, interleukin (IL) 1β, IL-2, interferon γ, IL-10, HLA-DR (human leukocyte antigen – DR isotype), C3, C4, C5, C1 complement inhibitors, C3a, C5a, IgA, IgM, IgG, CD3+CD4+, CD3+CD8+, CD3+CD56+, CD3+CD19+ can be considered as biomarkers of changes in the immune response in sepsis. In order to detect hemostasis disorders in sepsis, promising biomarkers may be: total platelet count, von Willebrand factor, factor VIII, protein C, thrombomodulin, tissue factor pathway inhibitor, tissue-type plasminogen activator, plasminogen activator inhibitor 1, thrombin activatable fibrinolysis inhibitor. Further study of the immunological and coagulation links of the pathogenesis of sepsis will make it possible to determine the key diagnostic and prognostic biomarkers of sepsis. We  analyzed 125 literature sources on  the eLibrary, Medline, PubMed, RSCI sites, of which 64 sources met our criteria for use in a systematic review.